Gender equality and American Jews - Hartman, Moshe, 1936- (SUNY series in American Jewish society in the 1990s., 1996)
Based on the 1990 National Jewish population survey, this book analyses gender equality in education, labour Force participation and occupational achievement among American Jews, and offers a comparison with the wider American population.